Upper limb extravasation injury following remifentanil infusion at the limb covered with adhesive wrapping for hypothermia prevention during anesthesia of pediatric patient - Mohamad Azlan Awang; Wan Mohd Nazaruddin Wan Hassan; Yusrina Zahari; Wan Azman Wan Sulaimana (Bali Journal of Anesthesiology, 2023)
We reported on a case involving a 41-day-old baby girl with a recurrent left supraglottic cyst and mild laryngomalacia who was scheduled for direct laryngoscopy and re-marsupialization. She sustained an extravasation injury following a remifentanil infusion during anesthesia, which was identified after the completion of surgery and the removal of surgical draping. The use of adhesive wrapping over the affected peripheral limbs to prevent hypothermia might have aggravated the ongoing extravasation injury. Immediate multidisciplinary management involving orthopedic and plastic reconstructive surgeries facilitated the smooth recovery of the patient. This case highlights the potential inadvertent complications that can arise intraoperatively during a continuous infusion of remifentanil in pediatric patients, as well as the aggravating factor of adhesive wrapping.